The Influence of Intrinsic Motivation and Supportive Leadership on Innovative Behavior through Career Sustainability and Psychological Safety of Employees in E-Commerce Companies in Indonesia - Griselda Nabila Fauzi; Putri Mega Desiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rapid development of technology has shifted the way of life to be more efficient, especially in e-commerce. Indonesia is predicted to lead the growth of global e-commerce by 2024 and the sector has faced the challenge of retaining competent employees to continue innovating. This study examines the influence of intrinsic motivation and supportive leadership on the innovative behavior of employees in Indonesian e-commerce companies, with career sustainability and psychological security as mediation. The data was collected through surveys of employees at Shopee, Tokopedia, Bukalapak, Blibli, and Lazada. The analysis using the PLS-SEM method with SmartPLS includes descriptive analysis, validity, reliability, and hypothesis testing. The results of the study stated that there was an influence of intrinsic motivation and supportive leadership on innovative behavior. Then, career sustainability mediates between supportive leadership and innovative behavior but does not mediate intrinsic motivation against innovative behavior in 186 Generation Z employees of Indonesian e-commerce companies. It is hoped that this study will be used as a reference for e-commerce companies in Indonesia to implement strategies in improving the innovative behavior of their employees.